Treatment of keloid scars with intralesional triamcinolone and 5-fluorouracil injections – a randomized controlled trial. Issue 1 (January 2019) - Hietanen, KE; Järvinen, TA; Huhtala, H; Tolonen, TT; Kuokkanen, HO; Kaartinen, IS
Summary: Keloids have high recurrence rates. Current first-line therapy is triamcinolone (TAC) injection, but it has been suggested that approximately 50% of keloids are steroid resistant. We compared the efficacy of intralesional 5-fluorouracil (5-FU) and triamcinalone injections in a double-blind randomized controlled trial. Forty-three patients with 50 keloid scars were treated with either intralesional TAC or 5-FU-injections over 6 months. There was no statistically significant difference in the remission rate at 6 months between the 5-FU and TAC groups (46% vs 60%, respectively). Local adverse effects were higher in the TAC group compared to the 5-FU group. Occurrence of skin atrophy in TAC group was 44% and in the 5-FU group 8% (p < 0.05). Also the occurrence of telangiectasia in the TAC group was 50% and in the 5-FU 21% (p < 0.05). Vascularity of the keloids, assessed by spectral imaging and immunohistochemical staining for blood vessels, after treatment decreased in the TAC group, but not in the 5-FU group (p < 0.05). Fibroblast proliferation evaluated by Ki-67 staining significantly decreased in the TAC group (p < 0.05) but increased in the 5-FU group (p < 0.05). TAC and 5-FU injections did not differ in their clinical effectivity in this randomized study, but 5-FU injections lead to increased proliferation rate and did not affect vascular density in histological assessment. Due to the greater number of adverse effects observed after TAC treatment, 5-FU injections may be preferable for cosmetically sensitive skin areas.